Sports Dance and the Process of Socialization - Adrianna Banio (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
The paper presents the socializing role of sports dance in man’s life. The influence of the activity or movement on the process of socialization of an individual and a group is multi-aspectual and plays significant role in social development of a human. Socialization through sports dance is described as one of the elements shaping character and influencing social communication, as well as affecting a man’s part in co-creation of the surrounding environment